1997
DOI: 10.1002/(sici)1097-4644(199704)65:1<107::aid-jcb11>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and tissue expression patterns of histone macroH2A1 subtypes

Abstract: MacroH2A is a novel nucleosomal core histone that contains a large nonhistone region and a region that closely resembles a full length histone H2A. We have cloned a cDNA that contains the entire coding region of macroH2A1.2, one of the two identified subtypes of macroH2A1. MacroH2A1.2 was found to differ from the other known subtype, macroH2A1.1, in a single segment of the nonhistone region. MacroH2A1 specific antibodies revealed relatively high levels of both subtypes in adult liver and kidney. MacroH2A1.1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
91
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 14 publications
9
91
1
2
Order By: Relevance
“…It has been suggested that macroH2A1.1 expression may be restricted to differentiated, non-proliferative tissues (Pehrson et al, 1997). To analyze any correlations between macroH2A1.1 protein expression and cell proliferation, we performed immunohistochemical stainings on tissue microarrays (TMAs) containing breast cancer samples of 260 patients (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that macroH2A1.1 expression may be restricted to differentiated, non-proliferative tissues (Pehrson et al, 1997). To analyze any correlations between macroH2A1.1 protein expression and cell proliferation, we performed immunohistochemical stainings on tissue microarrays (TMAs) containing breast cancer samples of 260 patients (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…We named these subtypes MACROH2A1.1 and MACROH2A1.2. The nucleotide sequences of cDNAs that encode MACROH2A1.1 and MACROH2A1.2 differed only in a single internal segment that encodes part of the nonhistone region (1,3), and these subtypes are formed by alternate splicing of a single gene, macroH2A1, on mouse chromosome 13 (4). Western blots of nuclear extracts from adult and fetal tissues revealed distinct tissue expression patterns that change during development (3).…”
mentioning
confidence: 99%
“…We identified two distinct MACROH2A cDNA sequences (1) and used specific antibodies to assign these sequences to the two MACROH2A proteins that were resolved by electrophoresis (3). We named these subtypes MACROH2A1.1 and MACROH2A1.2.…”
mentioning
confidence: 99%
“…Expression levels of macroH2A proteins correlate with the state of differentiation. 31,32 Loss of function approaches revealed a critical role for these histone variants in the differentiation but not the self-renewal of embryonic and adult stem cells. 34 Although macroH2As have well-characterized repressive functions, their influence on differentiation of embryonic stem cells is at least in part dependent on a pro-activating function of macroH2A1 on important differentiation regulatory genes such as Gata2 and Brachyury.…”
Section: Discussionmentioning
confidence: 99%
“…Plcγ1 is essential for erythropoietic differentiation TM Schnöder et al related gene product macroH2A1, are induced during various differentiation processes 31,32 and have been shown to contribute to the establishment and maintenance of the differentiated state. [33][34][35] Thus, we decided to investigate whether mH2A2 has a functional role in erythroid differentiation.…”
Section: Em (E) Quantitative Analysis (Paired T-test Two-tailed) Omentioning
confidence: 99%